Preoperative Prognostic Nutritional Index and Neutrophil-to-Lymphocyte Ratio Predict Survival Outcomes of Patients With Hepatocellular Carcinoma After Curative Resection - Qu, Zhen; Lu, Yun-jie; Feng, Jia-Wei; Chen, Yu-xiang; Shi, Long-qing; Chen, Jing; Rambaran, Navin; Duan, Yun-Fei; He, Xiao-zhou (Frontiers in Oncology, 2022)
Background: Increasing evidence showed that the preoperative prognostic indices were independent predictors of survival in patients with cancer. However, the validity of these indices are still controversial in patients with hepatocellular carcinoma (HCC). The aim of this study is to investigate the prognostic value of these indices in patients with HCC after curative hepatectomy. Methods: Data from 215 patients who underwent curative resection for HCC were retrospectively analyzed. All of the prognostic indices were compared by the area under the curve. Univariate analysis and multivariate analysis were performed to identify independent prognostic factors. Besides, risk factors were combined to predict the survival of patients. Results: Serum albumin, tumor diameter, tumor stage, degree of differentiation, prognostic nutritional index (PNI) and neutrophil-to-lymphocyte ratio (NLR) were independent prognostic factors for overall survival (OS). Vascular invasion, tumor stage, degree of differentiation and PNI were independent prognostic factors for recurrence-free survival (RFS). Patients with at least three risk factors had a significant lower OS and RFS compared with those with two or less risk factors. Conclusion: PNI and NLR could predict OS of patients with HCC after curative resection, and PNI is the predictor of RFS. Patients with more than two risk factors would have the worse survival.